Aspek Legalitas Perjanjian Kerja menurut Undang-Undang tentang Ketenagakerjaan pada Perusahaan Penerbangan - Dikha Anugrah; Haris Budiman; Anthon Fathanudien (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2021)
Work agreements give birth to work relationships which are the relationship between employers and workers based on work agreements, which have elements of work, wages, and orders. The emergence of a pilot contract case that reaches a dozen years is something that needs to be considered under the labor law. The purpose of this study was to determine and analyze the legal aspects of work agreements for pilots on Wings Air airlines, legal protection of pilots on Wings Air airlines and legal solutions that can be taken in cases of violations of work agreements against pilots on Wings Air airlines according to Law No. 13 of 2003 concerning employment. The method used is to use a critical paradigm which is to see phenomena that arise due to work agreements that are not in accordance with the Manpower Act. The results showed that the legal aspect of the work agreement for pilots on the wings air airline was that the Lion Air Group contract clause was in conflict with Labor Law No. 13 of 2003. Legal Protection of Pilots on Wings Air Airlines was that the employment contract that was valid for the dozen years were not in accordance with the law because the pilot's work did not comply with the provisions of the work agreement for a certain time so that the contract was null and void then changed to an indefinite time work agreement, and the status of the pilot became a permanent employee. Legal Settlement that Can Be Taken In Case of Violation of Work Agreement Against Pilots on Wings Air Airlines, among others, can be reached through Bipartite, Mediation, Conciliation, Arbitration, and Industrial Relations Court.